Formulation of optimal international freight transport objective - Jarašūnienė, Aldona (Transport, 2002)
To increase the attraction of Lithuania as a transit country striving to promote carriers' border crossing activities and facilitate customs clearance procedures as well as freight delivery to clients it is necessary to identity the main obstacles, to analyse them and to select adequate measures and means for their elimination. Therefore, on the basis of the formulation of transport freight management objective, as well as basing on the assessment of indeterminacy of external impacts, it would be possible to deduce the main causes of idle time of transport means in customs, to estimate the dependence of service time in proportion to transport flow.First Published Online: 19 Dec 2011